ENVIRONMENTAL JUSTICE AND URBAN GREEN SPACES WITH SPECIAL REFERENCE TO SHIMLA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
The health and well-being of individuals are profoundly impacted by things like urbanisation and climate change. In order to offset these negative health consequences, nature-based solutions that are implemented as natural and sustainable techniques in urban areas are a viable option. The purpose of this article is to investigate urban green spaces as an important nature-based solution that has the potential to solve difficulties connected to climate change and urbanisation by harnessing the services provided by urban ecosystems. The purpose of this article is to provide an overview of the link between urban green spaces and urban health. It illustrates how access to these areas may improve both physical and mental health; minimize health concerns associated to pollution, and increase general well-being. For the purpose of demonstrating how the uneven distribution of urban green spaces interacts with poor supply of ecosystem services and the beneficial health outcomes that are linked with them, the city of Shimla is utilized as a case study. The distribution of vulnerable population groups, such as children and old people, throughout the various city districts is the primary focus of the investigation. Both the discrepancies in access to green areas and the ways in which these disparities impact health outcomes are brought to light by the case study. This study also investigates the idea of environmental justice, focusing on the need of ensuring that everyone has equal access to green areas in order to advance the cause of health equality. The chapter emphasizes the significance of incorporating nature-based solutions into urban planning efforts in order to cultivate urban settings that are healthier and more resilient. This is accomplished by establishing a connection between the distribution of green areas and health outcomes and environmental justice.